Pain Management for Patients with Acute Myocardial Infraction: An Interventional Study for Nursing Staff - Hadeer Naeem Abdul-Hussein, Waffa Abed Ali Hattab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coronary artery disease is the most common type of heart disease. It encompasses a spectrum of clinical conditions ranging from asymptomatic atherosclerosis and stable or unstable angina to acute coronary syndrome caused by atheroma changes in the coronary arteries. It is one of the leading causes of death. Assessing risk factors for coronary artery disease and attaining the knowledge on how to deal with the symptoms’ pain is the first step in its prevention. Objective: To find out the effectiveness of an interventional program on Nurses’ knowledge and practices about pain management for patients with acute myocardial infraction at Coronary Care Units. Methodology: A pre-experiment design (one group pretest-posttest design) is applied has been done to obtain the study goals. A non- probability (purposive) sample was chosen to obtain representative and accurate data. From total (41) nurses working at CCU, (11) nurses were excluded from the educational program (five nurses for the pilot study, four nurses previously participated in pain management courses, and two nurse did not complete the program). The total number of nurses participating in the program of the study were (30) nurses. The sample had been taken in one group. The program is established and designed based on the preliminary assessment of nurses’ knowledge and practices about pain management for patients with acute MI at CCU, and also on the information obtained from the related scientific literatures and previous studies. The program content is reviewed by a group of experts. Statistical Package for Social Sciences (SPSS, version 23) was used to analyze the study data. Results of the study: The study findings presented that there was a highly significant differences of the knowledge between pre-test and post-test score at p value (.000), and a high significant difference between pre-test and post-test practices at p value (.000) related to pain management. Conclusion: The results of this study showed that the interventional program was an effective educational method that enables the nurses to improve their knowledge and practices towards pain assessment and management.